2010
DOI: 10.1002/ijc.24852
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of classical and nonclassical MHC class I expression in endometrial cancer

Abstract: The aim of this study was to investigate classical MHC class I and nonclassical MHC (human leukocyte antigen-G [HLA-G]) expression in a large cohort of patients with endometrial cancer, to determine the prognostic value of these cell surface markers and their relation with clinicopathological variables. Tissue microarrays containing epithelial endometrial carcinoma tissue from 554 patients were stained for classical and nonclassical MHC class I using the following monoclonal antibodies: 4H84 (anti-HLA-G), b2-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 48 publications
(74 reference statements)
6
56
2
Order By: Relevance
“…However, HLA class I downregulation did not have a significant influence on survival of patients with vulvar carcinoma. These results are in contrast to studies in endometrial [28], ovarian [33,34] and cervical cancer [31,35] where an association between downregulation of HLA class I and poor prognosis was observed.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, HLA class I downregulation did not have a significant influence on survival of patients with vulvar carcinoma. These results are in contrast to studies in endometrial [28], ovarian [33,34] and cervical cancer [31,35] where an association between downregulation of HLA class I and poor prognosis was observed.…”
Section: Discussioncontrasting
confidence: 99%
“…For immunostaining, tissue microarray slides were first dewaxed and rehydrated. Methods and antibodies for immunostaining of CD8 + T-lymphocytes, Foxp3 + T-lymphocytes, HLA-B/C and β 2 m were used as previously reported [22,28]. For HLA-A and IDO, antigen retrieval was performed by microwave treatment; 15 min in citrate (pH 6.0) (HLA-A), and EDTA buffer (pH 8.0) (IDO).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…These results indicated that as in normal immune situations, NLRC5 regulates MHC class I expression in human tumors. By analyzing the clinical data of 62 postoperative NSCLC stage III patients, it was determined that MHC class I and nuclear NLRC5 expression were independent predictors of poor survival, which was consistent with certain previous studies (7,21,22). In the present study, there was a high level of consistency among the 62 NSCLC patients, as they all underwent radical surgery and were diagnosed with stage III-N 2 NSCLC.…”
Section: A B Csupporting
confidence: 90%
“…Furthermore, the nuclear expression was found to be correlated with MHC class I. MHC class I heavy chain loss has been validated in a previous study to be a predictor of patient survival (22); the present study demonstrated that the expression of NLRC5 in the nucleus acted as a negative prognostic indicator in NSCLC patients. Therefore NLRC5 and MHC class I may be used in conjunction with other independent prognostic factors in order to further stratify patients for adjuvant therapy.…”
Section: A B Csupporting
confidence: 70%
“…23 It has also been reported that the status of HLA-G expression or sHLA-G levels in plasma was correlated with certain clinicopathological parameters in malignancies such as hepatocellular carcinoma (HCC), 24,25 nonsmall-cell lung cancer (NSCLC), 15,26,27 breast cancer, 28 endometrial carcinoma, 29 B-cell chronic lymphocytic leukemia (B-CLL), 30 gastric carcinoma and colorectal cancer. 31,32 These studies indicated that HLA-G might serve as a clinical marker in the diagnosis or prediction of clinical outcomes for malignant diseases.…”
mentioning
confidence: 99%